PEMBELAJARAN INKUIRI DAN METODE EKSPERIMEN TERBIMBING SERTA PENGARUHNYA TERHADAP HASIL BELAJAR KOGNITIF SISWA - Kristiana Nathalia Wea (Universitas Wiralodra, 2019)
This study aims to determine the effect and increase of cognitive learning outcomes of students using inquiry learning models with guided experimental learning methods on the subject of Newton's Law class X Santa Maria High School Yogyakarta. The research subjects of this study were class XB students and XE Santa Maria High School Yogyakarta. The total number of research subjects was 48 students. Class XB as the control class while the XE class as the experimental class. This research is an experimental research. The data used were the pretest scores of the experimental class students and the pretest scores of the control class students. This test was conducted using SSPS with a significant level of 0.05. The results of this study showed that there was no significant influence and improvement in cognitive learning outcomes between the experimental class and the control class. This is because students are not used to using inquiry learning models with guided experimental methods, so students are still hesitant to draw conclusions from the search